The Stabilization of a Hellenistic City Square (Plaza) at the Kınık Höyük Archeological Site, Niğde Province, Türkiye - Deniz Üçer Erduran; Burak Yolaçan; Lorenzo d’Alfonso (Buildings)
In recent years, at the Kınık Höyük archeological site in Niğde province in Turkey, a city square (plaza) located in the town’s acropolis was discovered. Context and spatial finds indicate that this stone-paved plaza dates to the Hellenistic era. It is made of a large cobblestone masonry structure made of local amorphous units that were fixed only with compacted earth. The conservation plan concentrated on enclosing the unbound free edges by using new pavement and a retaining wall to stop the ongoing decay because the plaza had already lost its integrity before the discovery. To distinguish between the original application and modern interventions, new cladding was designed and installed lower than the ancient pavement’s level using smaller stones from the same source. Additionally, a retaining wall was planned and built to be plastered to achieve a plain surface, where the pavement’s texture created contrast and highlighted neat craftsmanship. For this consolidation application, a hydraulic lime-based binder was combined with local earth for compatibility with the older application. The application’s suitability and durability were demonstrated after it was observed for a few years while being subjected to atmospheric impacts without any protection. Therefore, the examination confirmed that the suggested method is safe to apply in situations where similar stabilization needs arise.